Taxation and Economic Growth Nexus: Using ARDL and BOND Testing Procedures - Duramany-Lakkoh, Ezekiel Kalvin (Journal of Applied Business, Taxation and Economics Research, 2025)
This study analyses the nexus of taxation on economic growth using ARDL and BOND procedures. Pre-estimation tests were carried out to determine homoscedasticity, serial auto correlation, multicollinearity and normality of the variables. The coefficient of determination showed that 77.37 percent of the variation in GDP is explained by in direct taxes, other taxes, interest rate and foreign direct investment. The findings further revealed that the coefficient of indirect taxes was negative and individually significant in influencing the economic growth in Sierra Leone in the short run. On the other hand, the coefficients of interest rate are revealed to be positive and separately significant in affecting the economic growth in Sierra Leone in the short run. In view of these findings, it implies that indirect taxes increase consumption and reduce savings.